Phylogenetic inference and SSR characterization of tropical woody bamboos tribe Bambuseae (Poaceae: Bambusoideae) based on complete plastid genome sequences - Rogalski, Marcelo; Vieira, Leila do Nascimento; Anjo, Karina Goulart dos; Faoro, Helisson; Fraga, Hugo Pacheco de Freitas; Greco, Thiago Machado; Pedrosa, Fábio de Oliveira; Souza, Emanuel Maltempi de; Souza, Robson Francisco de; Guerra, Miguel Pedro (Current Genetics, 2015)
The complete plastome sequencing is an efficient option for increasing phylogenetic resolution and evolutionary studies, as well as may greatly facilitate the use of plastid DNA markers in plant population genetic studies. Merostachys and Guadua stand out as the most common and the highest potential utilization bamboos indigenous of Brazil. Here, we sequenced the complete plastome sequences of the Brazilian Guadua chacoensis and Merostachys sp. to perform full plastome phylogeny and characterize the occurrence, type, and distribution of SRRs using 20 Bambuseae species. The determined plastome sequence of Merostachys sp. and G. chacoensis is 136,334 and 135,403 bp in size, respectively, with an identical gene content and typical quadripartite structure consisting of a pair of IRs separated by the LSC and SSC regions. The Maximum Likelihood and Bayesian Inference analyses produced phylogenomic trees identical in topology. These trees supported monophyly of Paleotropical and Neotropical Bamboos clades. The Neotropical bamboos segregated into three well-supported lineages, Chusqueinae, Guaduinae, and Arthrostylidiinae, with the last two forming a well-supported sister relationship. Paleotropical bamboos segregated into two well-supported lineages, Hickeliinae and Bambusinae + Melocanninae. We identified 141.8 cpSSR in Bambuseae plastomes and an inferior value (38.15) for plastome coding sequences. Among them, we identified 16 polymorphic SSR loci, with number of alleles varying from 3 to 10. These 16 polymorphic cpSSR loci in Bambuseae plastome can be assessed for the intraspecific level of polymorphism, leading to innovative highly sensitive phylogeographic and population genetics studies for this tribe.
Keywords: Woody bamboos; Plastome; Next- generation; Molecular phylogeny; Poaceae